Assessment of Emotional Experience and Emotional Recognition in Complicated Grief - Fernández-Alcántara, Manuel; Cruz-Quintana, Francisco; Pérez-Marfil, M. N.; Catena-Martínez, Andrés; Pérez-García, Miguel; Turnbull, Oliver H. (Frontiers in Psychology, 2016)
There is substantial evidence of bias in the processing of emotion in people with complicated grief (CG). Previous studies have tended to assess the expression of emotion in CG, but other aspects of emotion (mainly emotion recognition, and the subjective aspects of emotion) have not been addressed, despite their importance for practicing clinicians. A quasi-experimental design with two matched groups (Complicated Grief, N = 24 and Non-Complicated Grief, N = 20) was carried out. The Facial Expression of Emotion Test (emotion recognition), a set of pictures from the International Affective Picture System (subjective experience of emotion) and the Symptom Checklist 90 Revised (psychopathology) were employed. The CG group showed lower scores on the dimension of valence for specific conditions on the IAPS, related to the subjective experience of emotion. In addition, they presented higher values of psychopathology. In contrast, statistically significant results were not found for the recognition of emotion. In conclusion, from a neuropsychological point of view, the subjective aspects of emotion and psychopathology seem central in explaining the experience of those with CG. These results are clinically significant for psychotherapists and psychoanalysts working in the field of grief and loss.